DICE-RD: An implementation of rate-related damages in the DICE model - Peter Michaelis; Heiko Wirths (Universität Augsburg, Institut für Volkswirtschaftslehre, 2019)
A growing body of literature from the natural and the social sciences indicates that the rate of temperature increase is another key driver of total climate damages, next to the absolute increase in temperature compared to the pre-industrial level. Nonetheless, the damage functions employed in integrated assessment models that aim at studying the economics of climate change are usually based on the absolute temperature increase alone. Hence, these models neglect additional damag-es that will occur if the rate of temperature increase exceeds a certain threshold that overstrains the adaptive capacities of ecological and social systems. In the present paper, we implement such rate-related damages in the well-known integrated assessment model DICE-2016R. Using the resulting model variant DICE-RD we show for several different scenarios that an insufficient climate policy that ignores rate-related damages can lead to substantial economic losses.
urn:nbn:de:bvb:384-opus4-710540
Keywords: O44; Q54; Q58; 330; integrated assessment; DICE model; climate policy; rate of temperature increase